European parliament and the european community - Herman, Valentine; Lodge, Juliet (London, 1978)
THis book examines the role of the European Parliament within the European Community. The introduction critically examines some traditional assumptions of direct elections for the powers of the EP, the role of the EP within the institutional set-up of the EC and the erelationship between the national parliaments of the member states of the EC and the EP..
Keywords: European Parliament